Pengaruh pijat Efflurage terhadap Produksi Air Susu Ibu pada Ibu Postpartum - Sefrina Rukmawati; Puji Astutik (LPPM UNIKAL, 2022)
Decreased milk production after giving birth can be caused by a lack of stimulation of the hormone prolactin and the hormone oxytocin which are very instrumental in the smooth flow of milk production. One massage that can launch milk production is effleurage massage. The purpose of this study was to determine the effect of effleurage massage on breast milk production in Mother Postpartum. This study used a pre-experimental research design with the One Group Pre-Post Test Design approach. The research population and samples is 12 respondents with a total sampling technique. The independent variable is effleurage massage and the dependent variable is milk production. Data collection using a observastion sheet. Data analysis using McNemar test with α = (0.05). The results of the study of 12 respondents, before being given effleurage massage, almost all respondents were 10 respondents whose milk production was not smooth (83.3%), while breast milk production after being given effleurage massage was almost all respondents, namely 11 respondents' milk production smoothly (91.7%). McNemar test results obtained pvalue = 0.004 ≤ α = (0.05), so that Ha is accepted. This shows that there is an influence of effleurage massage on the production of breast milk for Mother Postpartum in Kepanjen Village, Pace District, Nganjuk Regency. Effleurage massage is proven as an effort that can be done to expedite milk production, so that effleurage massage needs to be applied by the midwife / hospital.